Preliminary Study on Identification of Sociological Perspective to Landfill Management Facilities over Bakung landfill, Bandar Lampung, Sumatera - Novi Kartika Sari; Firdha Cahya Alam (Journal of Multidisciplinary Academic, 2020)
Solid waste disposal management is a great challenge to be socially accepted in many aspects. Unmanaged landfill is still commonly faced in Indonesia with characteristic of open dumping. Bakung Landfill located in Bandar Lampung It is one of them. The operation of landfill related to manage a facility can be negatively affected to who living near the landfill. Thus, in this study aimed to analyze sociological perspective of Bakung landfill by some influential factors. Here, forty samples had been collected by interviewing respondents with random sampling around 1 to 5 km in distance from landfill where Eight components consist of 35 questions in total were given to respondents. The components are covered a general information such as the existence of landfill, owner management, technology facilities availability, financial, social impact, nuisance, disturbance, and damaging environment. The Principal Component Analysis (PCA) and Cluster Analysis (CA) as comparison were conducted to identify data. Some statistical tools were done to filter data as quality assurance i.e. validity, reliability, normality and KMO test. Four new components were extracted and named by “facility management”, “pollution”, “financial and convenience”, and “technology to handling”. Facility management and pollution explained the top highest of total variance. CA had similar result with better visualization of the proximity of components. Many literatures supported the fact that unmanaged system in landfill related to the facility management was occurred and the pollution coming from landfill was exist. However, future research regarding institutional perspective and broader area of research need to be conducted to support the issues.